Gambaran Pola Asuh Orang Tua Pada Anak Berkebutuhan Khusus di SLBN-B Kabupaten Garut - Sri Yekti Widadi; Riyadi Rahman (STIKes Karsa Husada Garut, 2018)
Parenting is a form of parenting to instill discipline in their children that will ultimately shape the personality and behavior of children .. There are three types of parenting that authoritarian parenting, parenting democratic and permissive parenting. The purpose of this study to describe the parents' parenting on children with special needs (autism, deaf, Tunagrahita). The method used is descriptive with a sample of 96 people by using purposive sampling technique. Questionnaire data collection techniques. Analysis of the data used is univariate. The results, the majority of parents 64 (66.7%) applying the Democratic parenting on children with special needs. It is known that parents with children who suffer from autism than 10 parents most of which apply parenting Democratic as many as six people (60%), parents with children deaf majority of respondents are implementing parenting Democratic as many as 26 people (56%) and almost all of the respondents whose children Tunagrahita implement democratic parenting as many as 32 people (80%). The conclusion of this study is mostly elderly people applying parenting on children with special needs